That's So Last Season: Unraveling the Genomic Consequences of Fur Farming in Arctic Foxes ( Vulpes lagopus ) - Christopher A. Cockerill; J. Camilo Chacón‐Duque; Nora Bergfeldt; Johanna von Seth; Gabriella Björklund; Malin Hasselgren; Johan Wallén; Anders Angerbjörn; Eva Fuglei; Ester Rut Unnsteinsdottir; Paula White; Gustaf Samelius; et al. (Molecular Ecology, 2025)
Humans have relied on animal fur for centuries, yet fur farming only began recently during the mid‐19th Century. Little is known about this incipient domestication or the genomic processes involved. Domestication may involve founder effects, population bottlenecks and low population size, which, when combined with intense artificial selection, lead to inbreeding, a limited gene pool and reduced fitness. The arctic fox ( Vulpes lagopus ) has been farmed intensively since the early 1900s and has been artificially selected for economic phenotypes. We investigated the origin of these lineages and the genomic consequences of intensive farming by comparing the genomes of farmed and wild arctic foxes from across their range. Our research indicates recent inbreeding through long Runs of Homozygosity and reduced genomic variation in farmed foxes relative to their respective wild populations. We identified a coastal ecotype origin for all Fennoscandian farmed arctic foxes, aligning them phylogenetically with the wild Icelandic population, a geographically isolated and phenotypically distinct coastal lineage. The depleted genome‐wide heterozygosity and increased recent inbreeding in farmed fox lineages is consistent with a heavy consequence of domestication, shedding light on the demographic history and genomic consequences of human manipulation. We highlight the need for increased genomic investigations into fur farm populations to understand the incipient domestication process and uncover the cost of intense farming. The genomic consequences of domestication must be considered in the management of fur farms, with actionable steps needed to prevent descendants of escaped farmed foxes from polluting the gene pool in the wild through introgression.

Natal dispersal and exploratory forays through atypical habitat in the mountain‐bound snow leopard - Örjan Johansson; Justine Shanti Alexander; Purevjav Lkhagvajav; Charudutt Mishra; Gustaf Samelius (Ecology, 2024)

Increasing risks for emerging infectious diseases within a rapidly changing High Asia - Charudutt Mishra; Gustaf Samelius; Munib Khanyari; Prashanth Nuggehalli Srinivas; Matthew Low; Carol Esson; Suri Venkatachalam; Örjan Johansson (Ambio, 2022)
The cold and arid mountains and plateaus of High Asia, inhabited by a relatively sparse human population, a high density of livestock, and wildlife such as the iconic snow leopard Panthera uncia , are usually considered low risk for disease outbreaks. However, based on current knowledge about drivers of disease emergence, we show that High Asia is rapidly developing conditions that favor increased emergence of infectious diseases and zoonoses. This is because of the existing prevalence of potentially serious pathogens in the system; intensifying environmental degradation; rapid changes in local ecological, socio-ecological, and socio-economic factors; and global risk intensifiers such as climate change and globalization. To better understand and manage the risks posed by diseases to humans, livestock, and wildlife, there is an urgent need for establishing a disease surveillance system and improving human and animal health care. Public health must be integrated with conservation programs, more ecologically sustainable development efforts and long-term disease surveillance.

Examining the past and current distribution of Pallas’s cat in Southern Mongolia - Otgontamir Chimed; Justine Shanti Alexander; Gustaf Samelius; Purevjav Lkhagvajav; Lkhagvasuren Davaa; Narangarav Bayasgalan; Koustubh Sharma (Mammalian Biology, 2021)

Moving far, staying close: red fox dispersal patterns revealed by SNP genotyping - Zea Walton; Mari Hagenlund; Kjartan Østbye; Gustaf Samelius; Morten Odden; Anita Norman; Tomas Willebrand; Göran Spong (Conservation Genetics, 2021)
The genetic structure of a population can provide important insights into animal movements at varying geographical scales. Individual and social behaviors, such as philopatry and dispersal, affect patterns of relatedness, age and sex structure, shaping the local genetic structure of populations. However, these fine scale patterns may not be detected within broader population genetic structure. Using SNP genotyping for pairwise relatedness estimates, we investigated the spatial and genetic structuring of 141 red foxes within south-central Sweden at two scales. First, we looked at broad scale population structuring among red foxes at the regional level. We then estimated pairwise relatedness values to evaluate the spatial and genetic structure of male, female and mixed sex pairs for patterns of philopatry and dispersal at a more localized scale. We found limited genetic differentiation at the regional scale. However, local investigations revealed patterns of female philopatry and male biased dispersal. There were significant differences in pairwise geographic distances between highly related same sex pairs with the average distance between related males, 37.8 km, being six times farther than that of related females, averaging 6.3 km. In summary, the low levels of genetic differentiation found in this study illustrates the mobility and dispersal ability of red foxes across scales. However, relatedness plays a strong role in the spatial organization of red foxes locally, ultimately contributing to male biased dispersal patterns.

Traditional livelihoods under a changing climate: herder perceptions of climate change and its consequences in South Gobi, Mongolia - Tserennadmid Nadia Mijiddorj; Justine Shanti Alexander; Gustaf Samelius; Charudutt Mishra; Bazartseren Boldgiv (Climatic Change, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Long-distance dispersal in red foxes Vulpes vulpes revealed by GPS tracking - Zea Walton; Gustaf Samelius; Morten Odden; Tomas Willebrand (European Journal of Wildlife Research, 2018)

Spatial and temporal variation in the distribution and abundance of red foxes in the tundra and taiga of northern Sweden - David Carricondo-Sanchez; Gustaf Samelius; Morten Odden; Tomas Willebrand (European Journal of Wildlife Research, 2016)

Seasonal pulses of migratory prey and annual variation in small mammal abundance affect abundance and reproduction by arctic foxes - Gustaf Samelius; Ray T. Alisauskas; Serge Larivière (Polar Biology, 2011)

Sex-biased costs in nest defence behaviours by lesser snow geese (Chen caerulescens): consequences of parental roles? - Gustaf Samelius; Ray T. Alisauskas (Behavioral Ecology and Sociobiology, 2006)